The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1016/j.heliyon.2021.e08504
|View full text |Cite
|
Sign up to set email alerts
|

Psychology students' attitudes towards research: the role of critical thinking, epistemic orientation, and satisfaction with research courses

Abstract: The current study aimed to determine how attitudes towards research are related to epistemic orientation, critical thinking, and satisfaction with research courses in psychology university students. Control variables included respondents' gender, current academic degree (undergraduate or postgraduate), number of research methods courses completed, number of research projects completed, and academic score. A quantitative, cross-sectional design was used, with a non-probabilistic sample size of 137 students. Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…The differences observed may be due to the fact that on many occasions psychology students tend to have different experiences in teaching research, they are being more favored when research teachers demonstrate experience and current scientific production. In addition to this, the perception of disconnection between the content of research courses and their applicability to their professional field may also have an influence (Landa-Blanco & Cortés-Ramos, 2021) generating little interest in learning and applying the scientific method to solve practical problems in society, even when research priorities in the country are a guideline (Mamani-Benito et al, 2021). Another interesting finding has to do with the fact that students have a low opinion on the following: selfassessment of research skills (Self-Assessment dimension [SA]), the quality of human resources in research teaching (Faculty Impact [FIP]) and the promotion of research by the university where they study (Institutional Impact [IIP]).…”
Section: Discussionmentioning
confidence: 99%
“…The differences observed may be due to the fact that on many occasions psychology students tend to have different experiences in teaching research, they are being more favored when research teachers demonstrate experience and current scientific production. In addition to this, the perception of disconnection between the content of research courses and their applicability to their professional field may also have an influence (Landa-Blanco & Cortés-Ramos, 2021) generating little interest in learning and applying the scientific method to solve practical problems in society, even when research priorities in the country are a guideline (Mamani-Benito et al, 2021). Another interesting finding has to do with the fact that students have a low opinion on the following: selfassessment of research skills (Self-Assessment dimension [SA]), the quality of human resources in research teaching (Faculty Impact [FIP]) and the promotion of research by the university where they study (Institutional Impact [IIP]).…”
Section: Discussionmentioning
confidence: 99%
“…One way to achieve these 4C skills, especially for students at school, is for teachers to apply the quantum flipped learning model in high school physics learning [13]. Quantum learning (QL) is one of the clusters of inquiry learning models.…”
Section: Introductionmentioning
confidence: 99%
“…Further, this finding highlights disconnect between educators’ (and accrediting bodies’) opinions and those of students. It seems that the importance of research literacy as a graduate competency (e.g., APAC, 2019) is not effectively communicated to, or shared between, psychology students and instructors (Dempster & McCorry, 2017; Landa-Blanco & Cortés-Ramos, 2021; Uttl et al, 2013). As Strohmetz et al (2023) found, students tend to perceive these subjects to be about learning how to conduct research, an activity that many students believe they will not do after graduation (Murtonen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the students participating in the present study would not have taken a research subject (research subjects start in the second year of study at the authors’ institution); therefore, their lack of exposure to this content may have influenced their ratings. Future research is well-placed to undertake longitudinal testing across years of tertiary study to help identify if exposure and experience can change students’ perceptions of research subjects and whether this is impacted by the learning approach used (e.g., active learning approaches which make use of “real-life” data, Allen & Baughman, 2016; Landa-Blanco & Cortés-Ramos, 2021).…”
Section: Discussionmentioning
confidence: 99%